2021
DOI: 10.1088/1741-2552/ac1ed0
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-class motor imagery EEG classification method with high accuracy and low individual differences based on hybrid neural network

Abstract: Objective. Most current methods of classifying different patterns for motor imagery EEG signals require complex pre-processing and feature extraction steps, which consume time and lack adaptability, ignoring individual differences in EEG signals. It is essential to improve algorithm performance with the increased classes and diversity of subjects. Approach. This study introduces deep learning method for end-to-end learning to complete the classification of four-class MI tasks, aiming to improve the recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The CNN-LSTM network model uses 1D-CNN to extract the features of motor imaging EEG signals, motor imagination EEG as input to one-dimensional CNNs, and the data input dimension needs to become one-dimensional [11]. EEG signals obtained by multichannel EEG acquisition devices can be expressed as:…”
Section: Input Data Preprocessingmentioning
confidence: 99%
“…The CNN-LSTM network model uses 1D-CNN to extract the features of motor imaging EEG signals, motor imagination EEG as input to one-dimensional CNNs, and the data input dimension needs to become one-dimensional [11]. EEG signals obtained by multichannel EEG acquisition devices can be expressed as:…”
Section: Input Data Preprocessingmentioning
confidence: 99%
“…Although MI-EEGNET performed better than previous architectures, the high number of trainable parameters made it challenging to interpret. Besides these CNN architectures investigated for EEG signal classification, several studies can be found in the literature that used recurrent neural network (RNN) and its variants [21][22][23], such as LSTM and gated recurrent units (GRU), for the classification of mental tasks based on EEG signals [24,25]. However, RNNs are less prevalent in this area due to their exploding/vanishing gradient or lack of memory problems [26].…”
Section: Related Workmentioning
confidence: 99%
“…We then focus on the machine-learning methods used to detect patterns in the extracted EEG signal features. There are recent approaches using deep learning algorithms (Craik et al, 2019 ; Liu et al, 2021 ; Zhang et al, 2021 ; Lomelin-Ibarra et al, 2022 ). However, in biomedical applications with many features to take into account, still linear classifiers (e.g., SVM) or KNN classifiers are widely used (Mahmoudi and Shamsi, 2018 ).…”
Section: Introductionmentioning
confidence: 99%